Efficient Degradation of Phenol and 4‐Nitrophenol by Surface Oxygen Vacancies and Plasmonic Silver Co‐Modified Bi2MoO6 Photocatalysts. Issue 69 (21st November 2018) - Shen, Huidong; Xue, Wenwen; Fu, Feng; Sun, Jiefang; Zhen, Yanzhong; Wang, Danjun; Shao, Bing; Tang, Junwang
Abstract: In this work, the surface plasmon resonance effect of metallic Ag, surface oxygen vacancies (SOVs), and Bi2 MoO6 (BMO) material were rationally combined to construct new oxygen‐vacancy‐rich Ag/Bi2 MoO6 (A/BMO‐SOVs) photocatalysts. Their synergistic effect on the photocatalytic degradation of phenol and 4‐nitrophenol under visible‐light irradiation ( λ ≥420 nm) was also investigated. TEM, EPR, and Raman spectra demonstrate the co‐existence of metallic Ag nanoparticles, surface oxygen vacancies, and Bi2 MoO6 due to a controlled calcination process. The experimental results disclose that the 2 %A/BMO‐SOVs‐375 sample exhibited the highest photocatalytic activity for the degradation of both phenol and 4‐nitrophenol under visible‐light irradiation, achieving nearly 100 and 80 % removal efficiency, respectively, and demonstrated the apparent reaction rate constants ( k app ) 183 and 26.5 times, respectively, higher than that of pure Bi2 MoO6 . The remarkable photodegradation performance of A/BMO‐SOVs for organic substances is attributed to the synergistic effect between the surface oxygen vacancies, metallic Ag nanoparticles, and Bi2 MoO6, which not only improves the visible‐light response ability, but also facilitates charge separation. Thus, this work provides an effective strategy for the design and fabrication of highly efficient photocatalysts through integrating surface oxygen vacancies and the surface plasmon resonance effect of nanoparticles, which has the potential for both water treatment and air purification. Abstract : Let's work together ! A new oxygen‐vacancy‐rich Ag/Bi2 MoO6 photocatalyst was fabricated by a reliable solvothermal process combined with an impregnation–calcination approach. The photocatalyst exhibited excellent visible‐light‐driven photocatalytic performances for both phenol and 4‐nitrophenol degradation because of a synergistic effect stemming from the integration of the individual advantages of surface oxygen vacancies (SOVs), metallic Ag nanoparticles, and Bi2 MoO6 (BMO).